Education, laicism and religious pluralism. IRC and alternative activities in an intercultural perspective - Giuseppe Burgio; Marinella Muscarà (University of Bologna, 2020)
In Italian schools, some students benefit from the teaching of the Catholic religion, others choose not to use it. Among the latter, many - natives or immigrants - profess different religions. Others - natives or immigrants - declare themselves non-religious. Italian legislation provides for the creation of alternative school activities for them. This article will start from an examination of the epistemological models that regulate the teaching of religion in public schools in the European Union and, within this framework, the Italian model will be analysed as well as the reflection that has developed on the subject. This panorama will then be questioned from the concrete multicultural context in which we live, in order to propose a theoretical framework within which to reflect on alternative activities to the teaching of the Catholic religion. In order to do so, we will adopt an intercultural perspective focused on inclusion and dialogue between differences, in an attempt to recover educational objectives similar to those of the teaching of the Catholic religion.